San Francisco - Bing, Alison; Vlahides, John A.;Benson, Sara (Footscray, Victoria : Lonely Planet Publications, 2016)
Provides information on major points of interest, activities, accomodations, restaurants, shopping, transportation, and entertainment in the city.
Plan your trip -- Explore San Francisco -- Understand San Francisco -- Survival guide.
Includes index.
Keywords: GUIDEBOOKS